Enhanced spin Hall conductivity in tungsten-copper alloys - Coester, Birte (2022)
We report on the enhancement of the spin Hall conductivity in tungsten by alloying with copper, measured by using the spin-torque ferromagnetic resonance technique. The alloying leads to an increase in spin-dependent scattering events and results in an enhancement of the contributing extrinsic spin Hall effects. The measured damping property shows a slight increase with higher tungsten concentration, due to spin current losses from the ferromagnetic layer into the tungsten-copper alloy. At a tungsten concentration of 60%, the spin Hall conductivity reaches a maximum of 3.68±0.68×105Ω-1m-1, corresponding to an enhancement of 120% compared to the pure tungsten sample. At the same concentration, the ratio of the spin Hall angle to the damping of the ferromagnetic layer, which offers a quick estimation for the critical switching current density, is found to be four times smaller as compared to pure tungsten.